Analysis of Marketing Strategies for Sports Star Trading Cards - Shen, Yuan (Transactions on Social Science, Education and Humanities Research, 2024)
One of the reasons for the renewed interest in sports star trading cards is is a collection of things you love. For example, personal favorite team, personal favorite players, some people may be a memory of youth, and some people are a kind of walking with time now. Blind boxes, where collectors purchase a pack without knowing which cards they will receive, have become a popular marketing strategy to add an element of surprise and excitement to the buying experience. This unpredictability can create a sense of anticipation and increase the perceived value of the cards inside. Additionally, auctions of specific player cards can create a sense of competition among collectors, driving up prices and adding a thrill of the chase to the purchasing process. By analyzing the effectiveness of these marketing strategies, we can gain insights into what drives collectors to make purchases and how to best engage with them. Understanding these consumer behaviors can help companies in the sports star trading card market tailor their marketing efforts to maximize sales and increase collector engagement.